ArcGIS files for "A Remote Sensing Based Integrated Approach to Quantify the Impact of Fluvial and Pluvial Flooding in an Urban Catchment" - Muthusamy, Manoranjan (Cranfield University, 2020)
This ArcGIS contains merged DTM and DSM to produce the final terrain to compare fluvial and pluvial flood propoerties at Cockermouth during storm Desmend (2015). For more details please refer the following publication Muthusamy, Manoranjan, Monica Rivas Casado, Gloria Salmoral, Tracy Irvine, and Paul Leinster. 2019. €œA Remote Sensing Based Integrated Approach to Quantify the Impact of Fluvial and Pluvial Flooding in an Urban Catchment. Remote Sensing . doi:10.3390/rs11050577. Note: This folder contains DEM data downloaded from Environment Agency, UK. This metadata record is for Approval for Access product AfA458. Attribution statement: (c) Environment Agency copyright and/or database right 2019. All rights reserved.
Keywords: remote sensing data'; 'ArcGIS'; 'Environmental Science'; 'Hydrology'; 'Photogrammetry and Remote Sensing'